Thermosetting resin composition, and method for producing thermosetting resin composition
By mixing the polyester resin and the phenol oxidation resin in a specific proportion in the thermosetting resin composition, and using part of water or alcohol as solvent, the problems of poor storage stability of the composition under high temperature storage conditions and difficulty in adhesion to aluminum plates are solved, and excellent storage stability and adhesion properties are achieved.
Patent Information
- Application Number
- JP2023176152
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-23
AI Technical Summary
The conventional thermosetting resin composition has poor storage stability under high temperature storage conditions and has insufficient adhesion performance to substrates such as aluminum plates.
The use of the organic solvent is reduced by mixing the corresponding polyester resin and phenol oxidizing resin in a specific proportion (5/95 to 80/20), and adding part of water or alcohol to the composition.
It has achieved long-term low viscosity under high temperature conditions, avoided solidification, and showed excellent adhesion properties to substrates such as aluminum plates that are difficult to adhere to.
Smart Images

Figure 2025066497000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermosetting resin composition and a method for producing the thermosetting resin composition. In particular, the present invention relates to a thermosetting resin composition that has extremely excellent storage stability and exhibits excellent adhesion to poorly adhesive substrates such as aluminum plates, and to a method for producing the thermosetting resin composition. [Background technology]
[0002] Conventionally, polyimide molded products, such as polyimide films, have excellent chemical resistance, are insoluble in various solvents, and have a high melting point, making it difficult to melt and reuse them, unlike thermoplastic plastics such as polystyrene. Therefore, when polyimide molded products and the like are disposed of, most of them are either landfilled or incinerated, although this is expensive, which has resulted in problems of poor recyclability and poor environmental friendliness.
[0003] In view of this, a method has been proposed in which polyimide resin or polyimide, which is one of the industrial wastes that are discarded in large quantities, is subjected to alkaline hydrolysis together with metals (see, for example, Patent Document 1). More specifically, the present invention relates to a method for alkaline hydrolysis of polyimide, which comprises contacting a powder containing polyimide and having an average particle size of 30 μm or less with a basic aqueous solution.
[0004] Also, among the industrial wastes that are discarded in large quantities, another hydrolyzed polyimide resin has been proposed as a method for subjecting polyimide wastes to alkaline hydrolysis (see, for example, Patent Document 2). That is, the polyimide is reacted with 2 to 80 moles of hydroxyl ions (OH - The method for alkaline hydrolysis of polyimide is characterized in that the polyimide is decomposed into low molecular weight compounds by alkaline hydrolysis in the presence of a basic substance in an amount sufficient to produce a polyimide having a molecular weight of 100 or more and water as a reaction solvent.
[0005] Moreover, the applicant of the present invention has already proposed an imide group-containing compound solution having excellent storage stability (see, for example, Patent Document 3). More specifically, the imide group-containing compound solution contains an imide group-containing compound obtained by partially hydrolyzing a polyimide molded article, a solvent, and a viscosity stabilizer, and the viscosity stabilizer is an orthocarboxylic acid ester, a chelating agent, or either one of them. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-87148 A (Claims, etc.) [Patent Document 2] JP 2006-124530 A (Claims, etc.) [Patent Document 3] WO2015 / 079717 (Claims, etc.) Summary of the Invention [Problem to be solved by the invention]
[0007] However, the hydrolyzed polyimide resins of Patent Documents 1 and 2 react within 12 hours when stored at room temperature (25° C.), increase in viscosity, and gel, and thus have storage stability problems.
[0008] Furthermore, the imide group-containing compound solution of Patent Document 3 exhibits storage stability for about one month at room temperature (25°C), but when the storage temperature is raised to a relatively high temperature such as 40°C, the viscosity increases and gelation occurs in less than one month. In particular, in recent years, temperatures in warehouses and other storage locations have risen due to the effects of global warming, and long-term storage stability for approximately one to three months at relatively high temperatures of approximately 40°C has been required. Furthermore, when the imide group-containing compound solution of Patent Document 3 was applied to an aluminum plate or the like to form a coating film, there were cases in which the adhesion was insufficient and partial peeling occurred.
[0009] Therefore, after extensive research, the inventors of the present invention discovered that by blending a specified polyimide compound with a specified phenoxy resin, no increase in viscosity is observed over a long period of time (at least three months) even when stored at a relatively high temperature such as 40°C, and the coating film after application can exhibit excellent adhesion even to poorly adhesive substrates such as aluminum plates, and thus completed the present invention. That is, an object of the present invention is to provide a thermosetting resin composition that has excellent storage stability and can exhibit excellent adhesion to a substrate such as an aluminum plate, and an efficient method for producing such a thermosetting resin composition. [Means for solving the problem]
[0010] According to the present invention, there is provided a thermosetting resin composition comprising a phenoxy resin and an imide group-containing compound having a functional group reactive with the phenoxy resin (hereinafter, may be simply referred to as an imide group-containing compound), characterized in that the blending ratio (weight ratio) of the phenoxy resin / imide group-containing compound is 5 / 95 to 80 / 20, thereby solving the above-mentioned problems. That is, by using a specified phenoxy resin as one of the main components in combination with an imide group-containing compound having a functional group that reacts with the phenoxy resin, it is possible to obtain a thermosetting resin composition that has extremely excellent storage stability and can exhibit excellent adhesion to aluminum plates and the like in an extremely stable and economical manner.
[0011] In forming the thermosetting resin composition of the present invention, it is preferable that the phenoxy resin is in the form of an aqueous dispersion or aqueous emulsion, and the imide group-containing compound is an aqueous imide group-containing compound. By configuring in this way, it is possible to obtain a blend composition that does not substantially use organic solvents and that takes into consideration the impact on the environment.
[0012] In forming the thermosetting resin composition of the present invention, it is preferable that the epoxy equivalent of the phenoxy resin is set to a value within the range of 1,500 to 15,000. By configuring in this manner, the storage stability is extremely excellent and superior adhesion to aluminum plates and the like can be exhibited.
[0013] In forming the thermosetting resin composition of the present invention, it is preferable that the weight average molecular weight of the phenoxy resin is set to a value within the range of 1,000 to 100,000. By configuring in this manner, the storage stability is extremely excellent and superior adhesion to aluminum plates and the like can be exhibited.
[0014] In forming the thermosetting resin composition of the present invention, the imide group-containing compound is preferably an imide group-containing compound obtained by partially hydrolyzing a polyimide molded article. By configuring in this manner, by using a partially hydrolyzed imide group-containing compound in combination with a phenoxy resin, it is possible to obtain excellent storage stability as well as better adhesion in a more stable and economical manner.
[0015] In forming the thermosetting resin composition of the present invention, it is preferable that the weight average molecular weight of the imide group-containing compound is set to a value within the range of 1,000 to 100,000. By configuring in this manner, the storage stability is extremely excellent and superior adhesion to aluminum plates and the like can be exhibited.
[0016] In addition, when forming the thermosetting resin composition of the present invention, it is preferable that the composition further contains at least one particulate material selected from the group consisting of carbon particles, inorganic particles, inorganic oxide particles, nanoparticles, conductive particles, and semiconductor particles, and that the amount of the particulate material is within a range of 0.01 to 50% by weight based on the total amount. By configuring in this manner, the composition can be more suitably applied to various applications of thermosetting resin compositions that require heat resistance, mechanical properties, fluidity, heat shielding properties, infrared absorbing properties, electrical conductivity, semiconductivity, antistatic properties, colorability, and the like.
[0017] Another aspect of the present invention is a method for producing a thermosetting resin composition containing a phenoxy resin and an imide group-containing compound having a plurality of functional groups capable of reacting with the epoxy group, the method for producing a thermosetting resin composition comprising the following steps (1) to (3): (1) preparing a phenoxy resin (preferably an aqueous phenoxy resin); (2) A step of preparing an imide group-containing compound obtained by partially hydrolyzing a polyimide molded article. (3) A step of mixing the phenoxy resin / imide group-containing compound so that the compounding ratio is within a range of 5 / 95 to 80 / 20 to obtain a thermosetting resin composition. By carrying out the process in this manner, a thermosetting resin composition that has excellent storage stability at a relatively high temperature of 40° C. and exhibits superior adhesion to aluminum plates and the like can be obtained extremely stably and economically. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a diagram provided for illustrating the storage stability of a thermosetting resin composition when the blending ratio of the phenoxy resin / imide group-containing compound is changed. [Diagram 2] FIG. 2 is a diagram provided for illustrating the relationship between the curing temperature and the imidization rate of a thermosetting resin composition (A) containing a phenoxy resin and an imide group-containing compound and a thermosetting resin composition containing only an imide group-containing compound (hydrolyzate, B). [Diagram 3] FIG. 3 is a diagram provided to explain the effect on the adhesion of a coating film derived from a thermosetting resin composition when the blending ratio of the phenoxy resin / imide group-containing compound is changed (corresponding to Examples 1 to 8 and Comparative Examples 1 to 4). [Figure 4]FIG. 4 is a diagram provided to explain the effect on the heat resistance of a coating film derived from a thermosetting resin composition when the blending ratio of the phenoxy resin / imide group-containing compound is changed (corresponding to Examples 1 to 8 and Comparative Examples 1 to 4). [Diagram 5] FIG. 5 is a diagram provided to explain the effect on the surface hardness of a coating film derived from a thermosetting resin composition when the blending ratio of the phenoxy resin / imide group-containing compound is changed (corresponding to Examples 1 to 8 and Comparative Examples 1 to 4). [Figure 6] 6(a) to (d) are diagrams (photographs) provided to explain the state of the coating film surface after a boiling water resistance test for coating films derived from thermosetting resin compositions in which the blending ratio of phenoxy resin / imide group-containing compound was changed (corresponding to Examples 2, 3, and 5, and Comparative Example 1). [Figure 7] 7(a) and (b) are examples of FT-IR charts of the imide group-containing compound alone (hydrolysate) before and after curing, respectively. [Figure 8] 8(a) and (b) are examples of FT-IR charts of different imide group-containing compounds alone (hydrolysates) before curing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] [First embodiment] The first embodiment is a thermosetting resin composition (including its cured product) that contains a phenoxy resin and an imide group-containing compound having a functional group reactive with the phenoxy resin, and is characterized in that the blending ratio of the phenoxy resin / imide group-containing compound is within a range of 5 / 95 to 80 / 20. Hereinafter, the thermosetting resin composition of the first embodiment will be specifically described with respect to each constituent element.
[0020] 1. Phenoxy resin (1) Type A phenoxy resin is a high molecular weight epoxy compound obtained by reacting an epihalohydrin with a dihydric phenol compound, or a high molecular weight epoxy compound obtained by reacting a dihydric epoxy compound with a dihydric phenol compound. Therefore, examples of the phenoxy resin include bisphenol A type phenoxy resin, bisphenol F type phenoxy resin, bisphenol S type phenoxy resin, alicyclic phenoxy resin, aliphatic chain phenoxy resin, etc., either alone or in combination of two or more. The phenoxy resin is preferably an aqueous dispersion or an aqueous emulsion (sometimes collectively referred to as an aqueous phenoxy resin). Such an aqueous phenoxy resin can be used as a blending composition for a thermosetting resin composition that does not substantially use organic solvents and takes into consideration the impact on the environment. Furthermore, such an aqueous phenoxy resin has advantages in terms of production, such as ease of use and storage stability, and good uniform mixing and dispersibility with other compounding ingredients.
[0021] (2) Epoxy equivalent The phenoxy resin has an epoxy group in the molecule, and the epoxy equivalent is preferably set to a value within the range of 1,500 to 15,000 g / equivalent. The reason for this is that if the epoxy equivalent is less than 1,500 g / equivalent, it may react excessively with a predetermined imide group-containing compound, resulting in a decrease in the storage stability of the thermosetting resin composition. On the other hand, if the epoxy equivalent exceeds 15,000 g / equivalent, the reaction with a predetermined imide group-containing compound becomes excessively difficult, and the thermosetting resin composition may not exhibit excellent adhesion to a substrate. Therefore, it is more preferable to set the epoxy equivalent of the phenoxy resin to a value within the range of 1,800 to 12,000 g / equivalent, and further more preferable to set the epoxy equivalent to a value within the range of 2,000 to 8,000 g / equivalent. The epoxy equivalent of the phenoxy resin can be measured by a method in accordance with JIS K 7236.
[0022] (3) Weight average molecular weight The weight average molecular weight of the phenoxy resin is preferably set to a value within the range of 1,000 to 100,000. The reason for this is that if the weight average molecular weight is less than 1,000, the copolymer may react excessively with a predetermined imide group-containing compound, resulting in a decrease in the storage stability of the thermosetting resin composition. On the other hand, if the weight average molecular weight exceeds 100,000, the reaction with the predetermined imide group-containing compound becomes too difficult, and the thermosetting resin composition may not exhibit excellent adhesion to the substrate. Therefore, the weight average molecular weight of the phenoxy resin is more preferably set to a value within the range of 3,000 to 50,000, and even more preferably set to a value within the range of 5,000 to 30,000. The weight average molecular weight of the phenoxy resin can usually be measured as a polystyrene-equivalent molecular weight by using gel permeation chromatography (GPC).
[0023] (4) Storage stability Furthermore, by blending a predetermined amount of a specified phenoxy resin in a thermosetting resin composition, the storage stability can be significantly improved. That is, as shown in FIG. 1, in a thermosetting resin composition having a blending ratio of phenoxy resin / imide group-containing compound in a specified range (5 / 95 to 80 / 20), even at an environmental temperature of, for example, 40°C, the viscosity increase remains constant for three months or more, and excellent storage stability can be exhibited.
[0024] That is, the horizontal axis of FIG. 1 indicates the elapsed time (number of days), and the vertical axis indicates the viscosity (mPa / sec.) of the thermosetting resin composition (in a solution state). Moreover, characteristic curves A1 and A2 in FIG. 1 respectively show the change in viscosity at 25° C. and 40° C. of the thermosetting resin composition of the present invention in which the blending ratio of the phenoxy resin / imide group-containing compound is within a specified range (5 / 95 to 80 / 20). The characteristic curves B1 and B2 in FIG. 1 show the change in viscosity at 25° C. and 40° C., respectively, of a thermosetting resin composition substantially free of phenoxy resin.
[0025] Therefore, from the characteristic curves A1 and A2 in FIG. 1, it can be seen that the thermosetting resin composition of the present invention, in which the blending ratio of the phenoxy resin / imide group-containing compound is within a predetermined range, tends to show almost no change in viscosity for three months or more, whether the storage temperature is 25° C. or 40° C. On the other hand, from characteristic curves B1 and B2, it can be seen that the thermosetting resin composition not containing a phenoxy resin tends to increase in viscosity over time and not exhibit good storage stability. In particular, at a storage temperature of 40°C, the viscosity increases and the solution gels after one month, making viscosity measurement difficult. Therefore, by comparing the characteristic curves A1 and A2 with those of B1 and B2 in FIG. 1, it can be understood that if the blending ratio of the phenoxy resin / imide group-containing compound is within a specified range (5 / 95 to 80 / 20), the increase in viscosity is suppressed and excellent storage stability can be obtained over a long period of time (e.g., 3 to 6 months) without substantially blending a viscosity stabilizer.
[0026] (5) Thermosetting Furthermore, when a predetermined amount of a specific phenoxy resin is blended in a thermosetting resin composition, there is a tendency for the thermosetting property (imidization rate) of the imide group-containing compound, which is a partial hydrolyzate, to be hardly inhibited. That is, as shown in FIG. 2, in a thermosetting resin composition having a blending ratio of phenoxy resin / imide group-containing compound within a predetermined range (5 / 95 to 80 / 20), even when the heating temperature was changed from about 60 to 300°C and heat treatment was performed, no significant difference in thermosetting property was observed between the imide group-containing compound alone shown by characteristic curve B and the thermosetting resin composition shown by characteristic curve A. Therefore, it is understood that by blending a predetermined amount of a specific phenoxy resin in a thermosetting resin composition, only the storage stability is improved without significantly affecting the thermosetting properties.
[0027] (6) Adhesion / boiling water resistance Furthermore, with reference to FIG. 3 and FIG. 6, it will be explained that one of the properties of the thermosetting resin composition is that it has good adhesion. That is, the horizontal axis of FIG. 3 shows the blending ratio of the phenoxy resin to the imide group-containing compound, which is a hydrolyzate, in the thermosetting resin composition. The vertical axis indicates the evaluation (relative value) of adhesion in a specified boiling water resistance test, which is indicated as Evaluation 4 described later. Specifically, the thermosetting resin composition was applied to an aluminum plate in a predetermined thickness using a bar coater #50, dried at a temperature of 60 to 180°C for 30 minutes, and exposed to boiling water (98°C or higher) for 30 minutes. The adhesion was then evaluated (relative value). FIG. 6 shows photographs of the coating surfaces of Examples 2, 3 and 5 and Comparative Example 1 after the boiling water resistance test. It can be understood that, when the blending ratio of the phenoxy resin / imide group-containing compound is within a predetermined range (5 / 95 to 80 / 20), as shown in Figures 3 and 6, excellent adhesion can be obtained even after a predetermined boiling water resistance test against an aluminum plate, which is usually a poorly adherent substrate. In addition, in order to obtain an excellent adhesion evaluation even after a boiling water resistance test more stably and reliably, and furthermore to obtain the specified thermosetting property, heat resistance, etc., it has been found that the blending ratio of the phenoxy resin / imide group-containing compound is more preferably 10 / 90 to 45 / 55, and even more preferably 20 / 30 to 45 / 55.
[0028] (7) Heat resistance Next, referring to FIG. 4, one of the characteristics of the thermosetting resin composition is that good heat resistance can be obtained at a specific blend ratio of phenoxy resin / imide group-containing compound, which is a hydrolyzate. That is, the horizontal axis of FIG. 4 shows the blending ratio of the phenoxy resin to the imide group-containing compound, which is a hydrolyzate, in the thermosetting resin composition. The vertical axis indicates the evaluation (relative value) of the heat resistance test determined from the TG-DTA curve in accordance with JIS K 7120, which will be described later as Evaluation 6. From the characteristic curve in FIG. 4, it can be seen that if the blending ratio of the phenoxy resin / imide group-containing compound is within a specified range (5 / 95 to 80 / 20), sufficient heat curing occurs and an excellent heat resistance rating can be obtained.
[0029] (8) Surface hardness Furthermore, referring to FIG. 5, it will be described that, as one of the characteristics of the thermosetting resin composition, good surface hardness can be obtained at a certain blend ratio of phenoxy resin / hydrolyzed imide group-containing compound. That is, the horizontal axis of FIG. 5 shows the blending ratio of the phenoxy resin to the imide group-containing compound, which is a hydrolyzate, in the thermosetting resin composition. The vertical axis indicates a predetermined surface hardness evaluation (relative value) indicated as Evaluation 5 described later. From the characteristic curve in FIG. 5, it can be seen that if the compounding ratio of the phenoxy resin / imide group-containing compound is within a specified range (5 / 95 to 80 / 20), a sufficient curing reaction occurs and an excellent surface hardness can be obtained.
[0030] 2.Imide group-containing compounds (1) Type The imide group-containing compound constituting the thermosetting resin composition is characterized in that it has a plurality of functional groups capable of reacting with the epoxy groups of the phenoxy resin. That is, the imido group-containing compound has at least one of a carboxyl group, an amino group, a hydroxyl group, and the like, and thus functions as a crosslinking agent for the phenoxy resin. In addition, since the imide group-containing compound has a plurality of functional groups, it is possible for it to react with the phenoxy resin and also for it to undergo self-crosslinking upon heating at a low temperature.
[0031] (2) Partial hydrolyzate The imide group-containing compound is preferably a specific imide group-containing compound (sometimes referred to as a partial hydrolyzate or simply as an imide group-containing compound) obtained by partially hydrolyzing a polyimide molded article. The reason for this is that a partial hydrolyzate also has self-crosslinking properties at low temperatures (120° C. or lower), and the resulting cured product can have further improved heat resistance and weather resistance. In other words, partial hydrolysates have multiple functional groups, such as carboxyl groups, amino groups (including amide groups, the same applies below), and hydroxyl groups, within one molecule, and are capable of reacting with epoxy groups and of self-crosslinking when heated at low temperature.
[0032] FIG. 7(a) and FIGS. 8(a)-(b) show an example of a red spectroscopic chart (measured by ATR method) of a partial hydrolyzate before curing. The partial hydrolyzate is a polyimide compound having a predetermined structure and including a carboxyl group, an amino group (amide group), a hydroxyl group, etc. (compound A in FIG. 7). Fig. 7(b) shows an example of an infrared spectrum chart (measured by ATR method) of a partial hydrolyzate (compound A in Fig. 7) after thermal curing at 150°C for 30 minutes. That is, by comparing Figs. 7(a)-(b) and Fig. 8(a)-(b), it can be seen that the peaks of carboxyl groups, amino groups (amide groups), etc. are reduced and imide rings (peak A) are formed.
[0033] The partial hydrolyzates shown in Figures 7(a) and 8(a)-(b) have a wave number of 1375 cm -1 The absorption peak (peak A) derived from the imide group and the absorption peak at wavenumber 1600 cm -1 The absorption peak (peak B) derived from the amide group and the absorption peak (peak C) at 1413 cm -1 and an absorption peak (Peak C) derived from a carboxyl group. Therefore, such an imide group-containing compound has a wave number of 1500 cm in the infrared spectrum chart. -1 The absorption peak (peak D) due to the carbon of the benzene ring and the absorption peak at wave number 1710 cm -1It has an absorption peak (Peak E) derived from the carbonyl group, which can be used as a reference peak when performing qualitative analysis (identification) of compounds.
[0034] The partial hydrolysate is preferably an imide group-containing compound obtained by partially hydrolyzing a polyimide molded product of a predetermined size in the presence of water and a basic compound at a temperature of, for example, 50 to 100°C. Furthermore, such partial hydrolysates have at least imide groups, amide groups, and carboxyl groups, as well as carbonyl groups, etc., within the molecules consisting of carbon atoms, and thus are capable of relatively low-temperature curing (self-crosslinking) and reaction with the epoxy groups of the phenoxy resin. Furthermore, such partial hydrolysates can be said to be imide group-containing compounds that exhibit good solubility in various organic solvents and good adhesion to various substrates.
[0035] Here, it is presumed that the specific functional group of the partial hydrolyzate reacts with the epoxy group of the phenoxy resin, and when self-crosslinking occurs due to the specific functional group, the epoxy region (EP) and the polyimide region (PI) undergo a microphase separation phenomenon, forming a lamellar structure or the like. Therefore, as a reaction product of phenoxy resin and polyimide compound, it can exhibit good heat resistance, adhesion, and the like. Moreover, by containing polyimide compound regions bonded to the phenoxy resin / polyimide compound reaction product in predetermined positions, it is believed that the material exhibits a good balance of heat resistance, weather resistance, and other properties comparable to those of the polyimide compound alone.
[0036] In addition, if the compound contains an imide group and is obtained by hydrolysis, it is possible to recycle and reuse the so-called polyimide molded products. Therefore, the production cost of the partial hydrolysate can be further reduced, and thus an economically more advantageous thermosetting resin composition can be obtained.
[0037] Examples of polyimide molded products suitable for recycling include polyimide films, polyimide coatings, polyimide resists, polyimide electrical component housings, polyimide electronic component materials, polyimide containers, polyimide machine parts, polyimide automotive parts, and composite laminates such as circuit boards and TAB tapes in which a metal circuit pattern is formed on the surface of a polyimide film.
[0038] (3) Weight average molecular weight The weight average molecular weight of the imide group-containing compound is preferably set to a value within the range of 1,000 to 100,000. The reason for this is that by setting the weight average molecular weight in this range, a predetermined adhesiveness can be obtained and good solubility in organic solvents can be obtained. Therefore, the weight average molecular weight of the imide group-containing compound is more preferably set to a value within the range of 3,000 to 60,000, and even more preferably to a value within the range of 5,000 to 30,000. The weight average molecular weight of such an imide group-containing compound, like other compounds, can be measured by gel permeation chromatography as a polystyrene-equivalent molecular weight.
[0039] (4) Compounding amount It is also preferable to determine the blending amount of the imide group-containing compound in relation to the blending amount of the phenoxy resin by weight. That is, the phenoxy resin / imide group-containing compound are mixed so that the mixing ratio falls within the range of 5 / 95 to 80 / 20. The reason for this is that, in such a blending ratio of phenoxy resin / imide group-containing compound, if the blending amount of the imide group-containing compound is less than 20% of the total amount, the heat resistance, mechanical properties, weather resistance, etc. may be significantly reduced. On the other hand, in the blending ratio of the phenoxy resin / imide group-containing compound, if the blending amount of the imide group-containing compound exceeds 95%, the blending ratio of the phenoxy resin decreases relatively, and the coatability, flexibility, adhesion, storage stability (40°C, etc.), boiling water resistance, etc. of the thermosetting resin composition may be significantly reduced. Therefore, the blending ratio of the phenoxy resin / imide group-containing compound is more preferably within the range of 10 / 90 to 70 / 30, even more preferably within the range of 20 / 80 to 60 / 40, and even more preferably within the range of 30 / 70 to 60 / 40.
[0040] (5) Properties It is also preferred that the imide group-containing compound is a liquid, more specifically, that an aqueous solvent containing water or alcohol is used as the solvent, and that the blending amount of the aqueous solvent is usually within a range of 0.01 to 25% by weight based on the total amount of the imide group-containing compound. The reason for this is that such an imide group-containing compound, when in the form of an aqueous solution, is not only easy to handle, but also can be blended in an accurate ratio even with an aqueous phenoxy resin, etc., to form a more uniform thermosetting resin composition.
[0041] In addition, since the imide group-containing compound can be dissolved in a shorter time, it is also preferable to use an aqueous solvent in which an amine compound is dissolved in advance in part or in whole in water, alcohol, or the like (the concentration of the amine compound is, for example, 0.1 to 10% by weight). Examples of such amine compounds include aromatic amines, diamine compounds, and aromatic diamines having two amino groups bonded to an aromatic ring and a heteroatom other than the nitrogen atom of the amino groups. More specifically, at least one of dimethylaminoethanol, N,N-dimethylbenzylamine, phenylamine (=aniline), N,N-dimethylaniline, N,N-dimethyl-p-toluidine, 2-aminopyridine, tetrahydro-1,4-oxazidine (=morpholine), pyridine, hexahydropyridine (=piperidine), pyrrolidine, and the like can be mentioned. When the amine compound is added, the amount of the amine compound is preferably set to a value within a range of 0.1 to 30 parts by weight per 100 parts by weight of the imide group-containing compound contained in the imide group-containing compound, calculated as solid content.
[0042] 3. Solvent (1) Type 1 The type of solvent (including dispersion liquid) for the thermosetting resin composition is preferably basically water alone or water containing 0.1 to 30% by weight of an amine compound (amine-containing water). The reason for this is that if the solvent is water, then by heating the applied thermosetting resin composition at a temperature of at least 100°C or higher, and further at least 150°C or higher, the water can be easily and quickly dispersed, and it is possible to effectively prevent the water from remaining in the applied surface treatment film. Also, if the water contains a predetermined amount of the amine compound, the imide group-containing compound can be easily dissolved therein, and an aqueous solution of the imide group-containing compound having a predetermined concentration can be obtained.
[0043] (2) Type 2 On the other hand, depending on the application of the thermosetting resin composition, it is also preferable to mix an organic solvent with water, or to use an organic solvent alone as the solvent without using water. Examples of such organic solvents include at least one of N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide, N,N-dimethylacetamide, methyl diglyme, methyl triglyme, dioxane, tetrahydrofuran, cyclohexanone, cyclopentanone, γ-butyrolactone, toluene, ethyl acetate, butyl acetate, cellosolve, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and anisole.
[0044] (3) Compounding amount In addition, the amount of the solvent in the thermosetting resin composition is preferably set to a value within a range of 40 to 99% by weight relative to the total amount (100% by weight) of the thermosetting resin composition. The reason for this is that by adjusting the blending amount of the solvent to a predetermined range, the composition becomes easy to handle, the coating and drying become easy, and further, other blending components such as a thermoplastic resin component, a thermosetting resin composition component, a photocurable resin component, a metal material, a ceramic material, etc. can be blended uniformly and quickly.
[0045] More specifically, if the amount of the solvent is less than 40% by weight, the solubility of the imide group-containing compound and its mixability with the phenoxy resin become insufficient, resulting in a significant decrease in handleability. On the other hand, if the amount of the solvent exceeds 99% by weight, the viscosity will decrease excessively, making it difficult to form a uniform surface treatment film of the specified thickness and making precipitation more likely to occur. Therefore, the amount of the solvent is more preferably within a range of 50 to 90% by weight, and even more preferably within a range of 60 to 80% by weight, based on the total amount of the thermosetting resin composition.
[0046] 4. Viscosity stabilizer (1) Type It is also preferable to add a predetermined viscosity stabilizer to the thermosetting resin composition. Therefore, it is preferable to add at least one of a phytic acid compound, a dacro compound, EDTA, or the like. In other words, by adding a specific viscosity stabilizer, it is possible to function as a dehydrating agent and also to capture and chelate metal ions that are thought to cause pseudo-crosslinking derived from carboxyl groups and hydroxyl groups, thereby suppressing an increase in viscosity. Therefore, it has a low viscosity (100 to 100,000 mPsec, measurement temperature 20° C.) and can be easily filtered or easily made into a coatable state. However, even if the thermosetting resin composition does not substantially contain a viscosity stabilizer, by adding a predetermined amount of a phenoxy resin, an increase in the viscosity of the imide group-containing compound can be substantially prevented.
[0047] (2) Compounding amount The amount of the viscosity stabilizer is preferably within a range of 0.01 to 10 parts by weight, more preferably within a range of 0.1 to 7 parts by weight, and even more preferably within a range of 0.5 to 5 parts by weight, per 100 parts by weight of the imide group-containing compound (before the pseudo-crosslinked state). However, when the composition is made up of a combination of an imide group-containing compound and a phenoxy resin, these have a viscosity stabilizing effect, and therefore it is possible to substantially omit the incorporation of these viscosity stabilizers.
[0048] 5. Particulate matter (1) Type In addition, when forming the thermosetting resin composition, it is preferable to further contain at least one particulate material (including fibrous materials) selected from the group consisting of carbon particles, inorganic particles, inorganic oxide particles, nanoparticles, conductive particles, and semiconductor particles. The reason for this is that by containing particulate matter having an average particle size (equivalent sphere diameter or average major axis) measured in accordance with JIS Z 8901 of usually 0.01 to 500 μm, not only can the heat resistance, flowability, etc. of the thermosetting resin composition be easily adjusted, but also the mechanical properties, infrared absorbency, ultraviolet absorbency, electrical properties, density, colorability, etc. of the obtained cured product can be easily adjusted within desired ranges. Therefore, by blending particulate matter in this manner, the thermosetting resin composition can be more suitably applied to various applications requiring good heat resistance, mechanical properties, fluidity, heat insulation properties, electrical conductivity, colorability, etc.
[0049] More specifically, it is preferable to blend at least one of polyacetylene particles, polyaniline particles, polypyrrole particles, polythiophene particles, nickel particles, silver particles, copper particles, solder particles, silicon oxide, zinc oxide, aluminum oxide, zirconium oxide, titanium oxide, silica, glass particles, and the like. Furthermore, depending on the application, in order to improve various properties while ensuring the transparency of the thermosetting resin composition, it is also preferable to incorporate at least one type of nanoparticle, such as various nano-sized particles, metal oxide nanoparticles (ITO nanoparticles, IZO nanoparticles, IZTO nanoparticles, etc.), ceramic nanoparticles, nanopolyester fibers, nanocellulose fibers, nanopolyamide fibers, etc.
[0050] (2) Compounding amount Moreover, it is preferable that the blending amount of the particulate matter is generally set to a value within a range of 0.01 to 50 parts by weight when the total amount of the phenoxy resin and the imide group-containing compound is taken as 100 parts by weight. The reason for this is that if the blending amount of such particulate matter is less than 0.01 parts by weight, it becomes difficult to mix uniformly, and the blending effect may not be obtained. On the other hand, if the amount of such particulate matter exceeds 50 parts by weight, not only does it become difficult to adjust the transparency, heat resistance, fluidity, etc. of the thermosetting resin composition, but it may also become difficult to adjust the mechanical properties, electrical properties, density, etc. of the obtained cured product to fall within the desired range. Therefore, it is more preferable to set the amount of particulate matter within the range of 0.1 to 20 parts by weight, and even more preferable to set the amount of particulate matter within the range of 1 to 10 parts by weight, when the total amount of the phenoxy resin and the imide group-containing compound is 100 parts by weight.
[0051] 6.Viscosity Moreover, it is usually preferable that the viscosity of the thermosetting resin composition is set to a value within the range of 10 to 50,000 mPa·sec (measurement temperature: 25° C., solid content concentration: 20 to 60% by weight, the same applies below). The reason for this is that by limiting the viscosity to a predetermined range, not only is handling easy, but good storage stability can also be obtained. In addition, the coating properties are improved, and further, other components, such as a thermoplastic resin component, a thermosetting resin composition component, a photocurable resin component, a metal material, a ceramic material, etc., can be uniformly and quickly blended. Therefore, the viscosity of the thermosetting resin composition is more preferably set to a value within the range of 30 to 10,000 mPa·sec, and further preferably set to a value within the range of 50 to 1,000 mPa·sec. The viscosity of the thermosetting resin composition can usually be appropriately adjusted by adjusting the amount of the solvent for each of the phenoxy resin and the imide group-containing compound. Furthermore, the viscosity can be adjusted within a fine range by adjusting the average molecular weight of the phenoxy resin and the imide group-containing compound.
[0052] 7. Additives In addition, it is preferable to blend at least one additive such as an epoxy compound, a curing agent thereof, a curing accelerator thereof, a curing agent for an imide group-containing compound, a curing accelerator for an imide group-containing compound, an ultraviolet absorber, an antiaging agent, a conductive material, an antistatic agent, an infrared absorber, an elastomer, an adhesion improver, a dispersant, or a water repellent into the thermosetting resin composition of the present invention depending on the application, etc.
[0053] For example, in order to improve the storage stability of the thermosetting resin composition and further to adjust the surface smoothness of the obtained coating film, it is preferable to blend a specific surfactant different from the above-mentioned viscosity stabilizer. When a surfactant is added, the amount of the surfactant added is usually preferably set to a value within the range of 0.005 to 10% by weight relative to the total amount (100% by weight) of the thermosetting resin composition. The reason for this is that if the amount of the surfactant is less than 0.005% by weight, the added effect may not be manifested, whereas if the amount of the surfactant is more than 10% by weight, the heat resistance and mechanical strength of the resulting polyimide resin film may decrease.
[0054] 8.Applications The use of the thermosetting resin composition of the present invention is not particularly limited. For example, the composition can be used as a raw material for various resin films, resin molded products, metal films, metal molded products, ceramic films, and ceramic molded products, or as a thermosetting resin composition for impregnating paper or wood. In other words, although it depends on the compounding ratio of the phenoxy resin and the polyimide resin contained in the thermosetting resin composition, even if a large amount of the relatively inexpensive phenoxy resin is used and a small amount of the relatively expensive polyimide resin is used, it is possible to obtain a thermosetting resin composition and a cured product thereof that exhibit predetermined storage stability, excellent adhesion, heat resistance, surface hardness, flexibility, etc.
[0055] Therefore, the thermosetting resin composition of the first embodiment is suitable for at least one of a heat-resistant thermosetting resin composition, an ultraviolet-resistant thermosetting resin composition, a high-dielectric thermosetting resin composition, an electrical insulating thermosetting resin composition, a thermosetting resin composition for decorative materials, and the like. By thermally curing such a thermosetting resin composition at a predetermined temperature, it is possible to suitably obtain heat-resistant electrical component housings, heat-resistant electrical tapes, heat-resistant light-reflective tapes, heat-resistant electronic component molded products, heat-resistant circuit boards, heat-resistant containers, heat-resistant machine parts, heat-resistant automobile parts, ultraviolet absorbing molded products, ultraviolet absorbing films, and the like.
[0056] [Second embodiment] The second embodiment is a method for producing a thermosetting resin composition containing a phenoxy resin and an imide group-containing compound having a plurality of functional groups capable of reacting with the phenoxy resin, the method for producing a thermosetting resin composition being characterized by including the following steps (1) to (3): (1) A step of preparing a phenoxy resin as a phenoxy resin. (2) A step of preparing an imide group-containing compound obtained by partially hydrolyzing a polyimide molded article. (3) A step of mixing the phenoxy resin / imide group-containing compound at a compounding ratio of 5 / 95 to 80 / 20 to obtain a thermosetting resin composition. Hereinafter, the thermosetting resin composition of the second embodiment will be specifically described with respect to each constituent element.
[0057] 1. Phenoxy resin The phenoxy resin, including the aqueous phenoxy resin, can be similar to that described in the first embodiment, and therefore will not be described again here.
[0058] 2.Imide group-containing compounds The imide group-containing compound obtained by partially hydrolyzing the polyimide molded article can be the same as that described in the first embodiment, and therefore will not be described again here.
[0059] 3.Process 1 Step 1 is a step of preparing a specific phenoxy resin, preferably an aqueous phenoxy resin which is an aqueous dispersion or an aqueous emulsion. That is, this is a process in which the phenoxy resin described in the first embodiment is suspended in an aqueous solvent such as water or water containing an amine compound (amine-containing water) to prepare an aqueous phenoxy resin which is an aqueous dispersion or emulsion.
[0060] 4.Process 2 Step 2 is a step of preparing an imide group-containing compound obtained by partially hydrolyzing a polyimide molded article. That is, step 2 includes a preparation step of cutting the polyimide molded product to a predetermined size. Therefore, it is preferable to cut or classify polyimide molded articles as industrial waste or the like using a cutting device, a crushing device, a classifying device, or the like, to adjust the maximum width and average particle size in advance. That is, in order to enable more uniform and rapid partial hydrolysis, it is preferable to cut or classify the polyimide molded products as industrial waste or the like using a cutter, knife, chopper, shredder, ball mill, crusher, sieve, punching metal, cyclone, or the like, to adjust the maximum width or average particle size in advance.
[0061] More specifically, when the polyimide molded product is prepared into a strip shape, the average width is preferably 10 mm or less, more preferably within a range of 1 to 5 mm. When the polyimide molded product is adjusted to be granular, it is preferable that the average particle size measured in accordance with JIS Z 8901 is 10 mm or less, more preferably within the range of 1 to 5 mm. In order to further make the maximum width and average particle size uniform, it is preferable to feed the resulting mixture into a resin crusher equipped with a punching metal, a sieve, or the like while cooling it with dry ice or the like, and crush it into small pieces or granular polyimide crushed products.
[0062] Furthermore, step 2 includes a step of partially hydrolyzing a polyimide molded article of a predetermined size in the presence of at least water and a basic compound at a temperature of 40 to 100°C, more preferably at a temperature of 60 to 90°C, to obtain a crude imide group-containing compound. Therefore, it is preferable to hydrolyze the polyimide molded article in the presence of at least water and a basic compound at a predetermined temperature, for example, at normal pressure for 1 to 48 hours. Here, the basic compound means a compound that generates hydroxide ions, and examples thereof include sodium hydroxide, potassium hydroxide, calcium hydroxide, and sodium hydrogen carbonate.
[0063] By checking whether or not an absorption peak derived from an imide group, an absorption peak derived from an amide group, an absorption peak derived from a carboxyl group, etc., is present in an infrared spectroscopy chart obtained by infrared spectroscopy measurement, and further checking that the heights of each peak, and further the relative height ratios to the absorption peak derived from a benzene ring, etc., are within predetermined ranges, it can be confirmed whether or not a polyimide molded product has been partially hydrolyzed to obtain a desired crude imide group-containing compound.
[0064] 5.Process 3 Step 3 is a step of mixing the phenoxy resin / imide group-containing compound at a compounding ratio of 5 / 95 to 80 / 20 to obtain a thermosetting resin composition. That is, the aqueous phenoxy resin, which is the aqueous emulsion obtained in step 1, and the imide group-containing compound obtained in step 2 are mixed so that the blending ratio of the phenoxy resin / imide group-containing compound is 5 / 95 to 80 / 20, and a thermosetting resin composition is obtained, usually using a mixing device equipped with a stirrer. It is preferable to adjust the viscosity of such a thermosetting resin composition to 100 to 10,000 mPa·sec by adding an aqueous solvent such as water, water / alcohol, or amine water as a solvent.
[0065] 6.Process 4 Step 4 is a step of blending various additives into the thermosetting resin composition obtained in step 3. That is, this is a step of blending at least one of various additives such as an epoxy compound, a curing agent thereof, a curing accelerator thereof, a curing agent for an imide group-containing compound, a curing accelerator for an imide group-containing compound, an ultraviolet absorber, an antiaging agent, a conductive material, an antistatic agent, an infrared absorber, an elastomer, an adhesion improver, a dispersant, a water repellent, and a surfactant, as described in the first embodiment, depending on the application of the thermosetting resin composition, etc. Then, typically, a mixing device equipped with an agitator is used to prepare a thermosetting resin composition containing various additives.
[0066] 7.Process 5 Step 5 is a step of forming the thermosetting resin composition obtained in step 4 into various shapes and / or subjecting it to heat treatment to form a cured product. That is, step 5 is a step of forming the thermosetting resin composition obtained in step 4 into a sheet, plate, string, thread, or irregular shape by itself, or laminating it on various substrates to form a multilayer structure. Step 5 is a step of molding the thermosetting resin composition obtained in step 4 into various shapes, or applying it directly to various applications (filling material, electrical insulating material, semiconductor material, resist material, surface treatment material, heat-resistant material, light-shielding material, ultraviolet absorbing material, infrared absorbing material, etc.), and then heat-treating it.
[0067] 8.Other processes Other steps are steps of conducting various tests on the thermosetting resin composition molded into various shapes obtained in step 5, the thermosetting resin composition as obtained in step 4, and the cured product obtained by heat treatment or the like. That is, as will be evaluated in Example 1 described later, it is preferable to carry out a predetermined inspection process regarding the appearance, viscosity, storage stability, coatability, thermosetting property, adhesion, surface hardness, heat resistance, bending resistance, boiling water resistance, and the like of the thermosetting resin composition. EXAMPLES
[0068] The present invention will be described in further detail below with reference to examples.
[0069] [Example 1] 1. Preparation of thermosetting resin composition (1) Process (1) A Kapton film (mainly Kapton-100H but also a mixture of other Kapton films, manufactured by DuPont-Toray Co., Ltd.) serving as a polyimide molded product was cut into strips with a width of 10 mm or less using a chopper. Next, while cooling by adding dry ice, the mixture was put into a resin crusher (model number P-1314, HORAI Co., Ltd.) equipped with a punched metal of 3 mm in diameter, and the polyimide molded products (average particle size measured in accordance with JIS Z 8901: about 3 mm) that passed through the punched metal were used as polyimide crushed products to be partially hydrolyzed.
[0070] Next, 5 g of the obtained pulverized polyimide product, 400 g of ion-exchanged water, and 2 g of potassium hydroxide as a basic substance were placed in a 1,000 ml container equipped with a stirrer. Next, the temperature inside the vessel was raised to 50° C., and the contents were subjected to hydrolysis treatment for 24 hours while being stirred, to obtain a solution containing a crude imide group-containing compound.
[0071] Next, the solution containing the crude imide group-containing compound was subjected to a series of steps of acid treatment, water washing, alkali treatment, and water washing five times to purify the crude imide group-containing compound into a granular imide group-containing compound (average particle size measured in accordance with JIS Z 8901: 5 μm). Furthermore, it was confirmed by quantitative analysis that the granular imide group-containing compound contained approximately 0.2% by weight of potassium, approximately 0.02% by weight of Si, approximately 0.02% by weight of Ca, and 0.005% by weight of Fe.
[0072] Next, 300 g of an aqueous solvent was placed in a container equipped with a stirrer, and then 100 g of a granular (average particle size measured in accordance with JIS Z 8901: 0.3 mm) imide group-containing compound was added thereto, and the mixture was stirred with a stirrer until a uniform aqueous solution of the imide group-containing compound was obtained. Next, 100 g of water was further added as a diluent for the aqueous solution of the imide group-containing compound. At this stage, it is also possible to omit the addition of the viscosity stabilizer or to reduce the amount to about 1 / 2 to 1 / 10.
[0073] (2) Process (2) Next, a thermosetting resin composition was produced by mixing 30 parts by weight of an imide group-containing compound (aqueous imide group-containing compound / compound A) with 100 parts by weight of an aqueous phenoxy resin (manufactured by DIC Corporation, H502-42W, epoxy equivalent: 7600 mg / g, Type 1 in Table 1) in terms of solid content, and stirring until homogenized to obtain a thermosetting resin composition (solid content: about 30% by weight).
[0074] 2. Evaluation of thermosetting resin composition (1) Storage stability of thermosetting resin composition (Evaluation 1) The obtained thermosetting resin composition was allowed to stand at 40°C for 3 months, and the storage stability was evaluated in terms of the rate of viscosity change relative to the initial viscosity (B-type viscometer, room temperature, approximately 50 mPa sec) according to the following criteria. The results are shown in Table 2. ⊚: Viscosity increase is 3% or less of the initial viscosity. ◯: Viscosity increase is 30% or less of the initial viscosity. Δ: Viscosity increase is 100% or less of the initial viscosity. ×: The viscosity increase is more than 100% of the initial viscosity.
[0075] (2) Coating ability of thermosetting resin composition (Evaluation 2) The obtained thermosetting resin composition was applied to aluminum plates (thickness 0.3 mm, A1050P) using different bar coater sizes (#28, 50, 60, 70, 75) to form coating films with different thicknesses. The thickness that could be uniformly applied was measured and the coatability was evaluated. The results are shown in Table 2. ◎: A uniform coating film can be formed in the range of 5 to 40 μm. ◯: A uniform coating film can be formed in the range of 5 to 30 μm. △: A uniform coating film can be formed in the range of 5 to 20 μm. ×: A uniform coating film could not be formed within the range of 5 to 20 μm.
[0076] (3) Thermosetting (Rating 3) The obtained thermosetting resin composition was applied to an aluminum plate (thickness: 0.3 mm) using a bar coater to form a coating film of 20 μm, which was then air-dried at room temperature. Next, heat curing treatments were performed at 180°C for 30 minutes, 220°C for 30 minutes, and 250°C for 30 minutes to find the conditions under which the pencil hardness of the coating surface was H or higher. The heat curing properties were evaluated according to the following criteria, and the results are shown in Table 2. ◎: After heat curing treatment at 180℃ for 30 minutes, the pencil hardness of the coating surface is H or higher. ◯: After heat curing treatment at 220℃ for 30 minutes, the pencil hardness of the coating surface is H or higher. △: After heat curing treatment at 250℃ for 30 minutes, the pencil hardness of the coating surface is H or higher. ×: After heat curing treatment at 250℃ for 30 minutes, the pencil hardness of the coating surface is less than H.
[0077] (4) Adhesion (rating 4) The obtained thermosetting resin composition was applied to an aluminum plate (thickness: 0.3 mm) using a bar coater to form a coating film having a thickness of 20 μm, and the coating film was air-dried at room temperature. Next, a heat curing treatment was performed at 200°C for 30 minutes, and then a cross-cut test (a total of 100 cross-cuts of 2 mm x 2 mm) was performed in accordance with JIS K 5600-5-6 to evaluate the adhesion according to the following criteria. The results are shown in Table 2. ⊚: The number of peeled off pieces is 1 or less per 100 grids. ◯: The number of peeled off pieces is 2 to 5 per 100 grids. △: The number of peeled off pieces is 6 to 15 per 100 grids. ×: The number of peeled off pieces is 16 or more per 100 grids.
[0078] (5) Surface hardness (rating 5) The obtained thermosetting resin composition was applied to an aluminum plate (thickness: 0.3 mm) using a bar coater to form a coating film having a thickness of 20 μm, and the coating film was air-dried at room temperature. Next, after heat curing treatment at 200° C. for 30 minutes, a pencil hardness test was carried out in accordance with JIS K 5600-5-4 to evaluate the adhesion according to the following criteria. The results are shown in Table 2. ⊚: Pencil hardness is H or higher. A: The pencil hardness is HB or higher. △: Pencil hardness is B or higher. ×: The pencil hardness is less than B.
[0079] (6) Heat resistance (rating 6) The obtained thermosetting resin composition was applied to an aluminum plate (thickness: 0.3 mm) using a bar coater to form a coating film having a thickness of 20 μm, and the coating film was air-dried at room temperature. Next, a coating film was obtained by heat curing treatment at 200°C for 30 minutes, and a measurement sample was taken from it. Next, in accordance with JIS K 7120, a thermobalance (TG-DTA analyzer manufactured by Mettler) was used to heat the sample from 30 to 500° C. (heating rate: 10° C. / min) in a nitrogen stream of 100 ml / min to obtain a TG-DTA curve. Next, the heat resistance of the obtained measurement sample (polyimide resin film) was evaluated based on the TG curve out of the TG-DTA curves, according to the following criteria. The results are shown in Table 2. ◎: 10% weight loss temperature is 350°C or higher. ◯: The 10% weight loss temperature is 300° C. or higher. △: 10% weight loss temperature is 200°C or higher. ×: The 10% weight loss temperature is less than 200°C.
[0080] (7) Bending resistance (rating 7) The obtained thermosetting resin composition was applied to an aluminum plate (thickness: 0.3 mm) using a bar coater to form a coating film having a thickness of 30 μm, and the coating film was air-dried at room temperature. Next, after performing a heat curing treatment at 200°C for 30 minutes, the obtained coating film with the aluminum plate was wrapped around a cylinder with a diameter of 3 mm and bent at 180° in accordance with JIS K 5600-5-1, and the bending resistance of the coating film (polyimide resin film) was evaluated according to the following criteria, and the obtained results are shown in Table 2. ⊚: No change in appearance such as cracks or whitening was observed in the coating film. ◯: Almost no change in appearance such as cracks or whitening was observed in the coating film. Δ: Slight changes in appearance such as cracks or whitening are observed in the coating film. ×: Significant changes in appearance such as cracks and whitening are observed in the coating film.
[0081] (8) Boiling water resistance (rating 8) The obtained thermosetting resin composition was applied to an aluminum plate (thickness: 0.3 mm) using a bar coater to form a coating film having a thickness of 20 μm, and the coating film was air-dried at room temperature. Next, after a heat curing treatment at 200°C for 30 minutes, the resulting coating film with the aluminum plate was immersed in boiling water heated to a temperature of 98°C or higher for 30 minutes to evaluate the boiling water resistance of the coating film. The results are shown in Table 2. ⊚: No change in appearance such as cracks or peeling was observed in the coating film. ◯: Almost no change in appearance such as cracks or peeling is observed in the coating film. Δ: Slight changes in appearance such as cracks or peeling are observed in the coating film. ×: Significant changes in appearance such as cracks and peeling are observed in the coating film.
[0082] [Example 2] In Example 2, the imide group-containing compound was mixed in an amount of 100 parts by weight to 100 parts by weight of the phenoxy resin (Type 1) in terms of solid content, and the mixture was stirred until homogenous to obtain a thermosetting resin composition (solid content: approximately 30% by weight). The thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1.
[0083] [Example 3] In Example 3, the type of aqueous phenoxy resin was H505-42W (Type 2 in Table 1) manufactured by DIC Corporation, and 300 parts by weight of an imide group-containing compound was mixed with 100 parts by weight of the phenoxy resin, and the mixture was stirred until homogeneous to obtain a thermosetting resin composition (solid content: approximately 30% by weight). Except for this, the thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1.
[0084] [Example 4] In Example 4, the type of aqueous phenoxy resin was PKHW-34 (Type 3 in Table 1) manufactured by HUNTSMAN, and 500 parts by weight of an imide group-containing compound was mixed with 100 parts by weight of the phenoxy resin in terms of solid content, and the mixture was stirred until homogeneous to obtain a thermosetting resin composition (solid content: approximately 30% by weight). Except for this, the thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1.
[0085] [Example 5] In Example 5, the imide group-containing compound was mixed in an amount of 800 parts by weight relative to 100 parts by weight of the phenoxy resin (Type 3) in terms of solid content, and the mixture was stirred until homogenous to obtain a thermosetting resin composition (solid content: approximately 30% by weight). The thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1.
[0086] [Example 6] In Example 6, the imide group-containing compound was mixed in an amount of 2000 parts by weight relative to 100 parts by weight of the phenoxy resin (Type 3) in terms of solid content, and the mixture was stirred until homogenous to obtain a thermosetting resin composition (solid content: approximately 30% by weight). The thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1.
[0087] [Example 7] In Example 7, two types of phenoxy resins were used (Typ1 / Typ2=50 parts by weight / 50 parts by weight) in terms of solid content, and 25 parts by weight of an imide group-containing compound was mixed with 100 parts by weight of the two types of phenoxy resins, and the mixture was stirred until homogeneous to obtain a thermosetting resin composition (solid content: approximately 30% by weight). Except for this, the thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1.
[0088] [Example 8] In Example 8, three types of phenoxy resins were used (Typ1 / Typ2 / Typ3=50 parts by weight / 25 parts by weight / 25 parts by weight) in terms of solid content, and 50 parts by weight of an imide group-containing compound was mixed with 100 parts by weight of the three types of phenoxy resins, and stirred until homogenous to obtain a thermosetting resin composition (solid content: approximately 30% by weight). Except for this, the thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1.
[0089] [Comparative Example 1] In Comparative Example 1, the thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1, except that no phenoxy resin (Type 1) was used, and only a specific imide group-containing compound was used.
[0090] [Comparative Example 2] In Comparative Example 2, the thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1, except that the amount of the specified imide group-containing compound was 4 parts by weight per 100 parts by weight of the phenoxy resin (Type 1).
[0091] [Comparative Example 3] In Comparative Example 3, the thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1, except that only the phenoxy resin (Type 1) was used and the specified imide group-containing compound was not blended.
[0092] [Comparative Example 4] In Comparative Example 4, the thermosetting resin composition and the coating film were evaluated in the same manner as in Example 1, except that the amount of a specified imide group-containing compound was 30,000 parts by weight per 100 parts by weight of the phenoxy resin (Type 3).
[0093] [Table 1]
[0094] [Table 2] [Industrial Applicability]
[0095] As described above, according to the present invention, by blending a specific phenoxy resin and an imide group-containing compound having a specific structure obtained by hydrolysis in a specific ratio, it is possible to provide a thermosetting resin composition having excellent long-term storage stability at relatively high temperatures (e.g., 40°C) and excellent adhesion even to poorly adhesive substrates, and an efficient method for producing the same. That is, the imide group-containing compound having a specific structure obtained by hydrolysis has a problem of being extremely self-reactive and poor in storage stability, and therefore it is necessary to compound a specific viscosity stabilizer. However, when a thermosetting resin composition is formed by combining an imide group-containing compound having a specific structure obtained by hydrolysis with a specific phenoxy resin, good storage stability and pH retention can be obtained even when the incorporation of a specific viscosity stabilizer is omitted.
[0096] Furthermore, according to the thermosetting resin composition of the present invention, by blending a predetermined phenoxy resin and an imide group-containing compound having a specific structure obtained by hydrolysis in a predetermined ratio, it is possible to form a thick film, for example, of 20 to 50 μm, on various substrates (e.g., aluminum plate, copper plate, iron plate, zinc plate, olefin resin plate, polyester resin plate, polycarbonate resin plate, ABS resin plate, ceramic resin plate, glass plate, wooden plate, etc.) by carrying out a single coating step.
[0097] That is, in the case of a conventional combination of a specific epoxy compound or the like and an imide group-containing compound having a specific structure obtained by hydrolysis, a coating film of only about 5 to 15 μm could usually be formed by carrying out a single coating step. Therefore, in order to obtain a thick film of 20 μm or more, it is usually necessary to apply multiple layers in multiple stages, which tends to cause problems such as delamination.
[0098] In contrast, in the case of the thermosetting resin composition of the present invention, it is believed that the blending of a specific phenoxy resin makes it easy to optimize the surface free energy, and also makes it easy to form a coating film of a desired thickness. In turn, this results in the unexpected effect of making the handling and production itself extremely easy and stable, and significantly increasing versatility.
[0099] Furthermore, according to the thermosetting resin composition of the present invention, so long as the specified imide group-containing compound is a partial hydrolyzate obtained by partially hydrolyzing a polyimide molded article as a so-called recycled product, even when it is combined with a specified phenoxy resin, it is possible to provide a thermosetting resin composition and a production method thereof that are inexpensive and economical overall.
Claims
1. A thermosetting resin composition comprising a phenoxy resin and an imide group-containing compound having a plurality of functional groups capable of reacting with the phenoxy resin, A thermosetting resin composition characterized in that the blending ratio of the phenoxy resin to the imide group-containing compound is 5 / 95 to 80 / 20.
2. 2. The thermosetting resin composition according to claim 1, wherein the phenoxy resin is in the form of an aqueous dispersion or an aqueous emulsion, and the imide group-containing compound is an aqueous imide group-containing compound.
3. 3. The thermosetting resin composition according to claim 1, wherein the epoxy equivalent of the phenoxy resin is set to a value within a range of 1,500 to 15,000.
4. 3. The thermosetting resin composition according to claim 1, wherein the weight average molecular weight of the phenoxy resin is within a range of 1,000 to 100,000.
5. 3. The thermosetting resin composition according to claim 1, wherein the imide group-containing compound is an imide group-containing compound obtained by partially hydrolyzing a polyimide molded article.
6. 3. The thermosetting resin composition according to claim 1, wherein the weight average molecular weight of the imide group-containing compound is within a range of 1,000 to 100,000.
7. 3. The thermosetting resin composition according to claim 1, further comprising at least one particulate material selected from the group consisting of carbon particles, inorganic particles, inorganic oxide particles, nanoparticles, conductive particles, and semiconductor particles, and the amount of the particulate material is within a range of 0.01 to 50% by weight based on the total amount of the thermosetting resin composition.
8. A method for producing a thermosetting resin composition containing a phenoxy resin and an imide group-containing compound having a functional group capable of reacting with the phenoxy resin, the method for producing a thermosetting resin composition comprising the steps of: (1) preparing the phenoxy resin; (2) A step of preparing the imide group-containing compound by partially hydrolyzing a polyimide molded article. (3) A step of mixing the phenoxy resin and the imide group-containing compound in a compounding ratio of 5 / 95 to 80 / 20 to obtain the thermosetting resin composition.
Citation Information
Patent Citations
JP124530A
Method for alkaline hydrolysis of polyimide and method for recovery of low molecular weight compound and metal from polyimide metal laminate
JP2013087148A
Imide group-containing compound solution and production method for polyimide film derived from imide group-containing compound solution
WO2015079717A1